Ecdysterone receptor is a sequence-specific transcription factor involved in the developmental regulation of heat shock genes. - Luo, Y.; Amin, J.; Voellmy, R. (Molecular and Cellular Biology, 1991)
Purification of ecdysterone receptor from Drosophila melanogaster to apparent homogeneity is reported. Purified receptor binds specifically to several sequences in the promoters of the developmentally active hsp27 and hsp23 heat shock genes that were previously implied in ecdysterone regulation of the genes and that share limited homology among themselves and with mammalian steroid receptor binding sites. Some of these elements confer ecdysterone regulation on a basal promoter in transfected cells, acting in a synergistic fashion. Transcription in vitro of promoters containing such elements is stimulated up to 100-fold by added purified ecdysterone receptor, depending on receptor dosage and the number of elements present. Transcriptional enhancement requires sequence-specific binding of receptor to template promoters which facilitates the formation of a preinitiation complex. Ecdysterone stimulates DNA binding of the receptor in vitro.